Emerging technologies in computing : theory, practice, and advances - Kumar, Pramod; Tomar, Anuradha; Sharmila, R. (Boca Raton : CRC Press, 2022)
Emerging Technologies in Computing: Theory, Practice, and Advances reviews the past, current, and future needs of technologies in the computer science field while it also discusses the emerging importance of appropriate practices, advances, and their impact. It outlines emerging technologies and their principles, challenges, and applications as well as issues involved in the digital age. With the rapid development of technologies, it becomes increasingly important for us to remain up-to-date on new and emerging technologies. It draws a clear illustration for all those who have a strong interest in emerging computing technologies and their impacts on society. Features: Includes high-quality research work by academicians and industrial experts in the field of computing Offers case studies related to Artificial Intelligence, Blockchain, Internet of Things, Multimedia Big data, Blockchain, Augmented reality, Data Science, Robotics, Cybersecurity, 3D printing, Voice Assistants and Chatbots, and Future Communication Networks Serves as a valuable reference guide for anyone seeking knowledge about where future computing is heading
About the EditorsList of ContributorsIntroduction to Emerging Technologies in Computer Science and its ApplicationsUmang Kant, Vinod KumarArtificial Intelligence Innovations: Infrastructure and Application for Advances in Computational SupremacyShruti Gupta, Ashish Kumar, Pramod Kumar, Pastor ArguellesEssentials of Internet of Things: Design principles and Architectures for its Application in various domains Hariprasath Manoharan, Abirami Manoharan, Shankar T, Yuvaraja T, Dineshkumar AmbalavananTheories of Blockchain: Its Evolution and Application for Security, Privacy and Trust ManagementNavneet AroraAdvances in Robotic Systems: Design, Modeling, Development and Control PrinciplesPriyanka Dhuliya, Piyush Dhuliya, Sunil SemwalData Science Practices:Running the Data Experiments Effectively for Statistical and Predictive Analytics on Data Aatif Jamshed, Asmita Dixit, Amit Sinha, Kanika Gupta, Manish KumarThe Actuality of Augmented Reality: Understanding the realm of the Theoretical framework for embracing its potential facilities Ruchi Goel, Pavi Saraswat, Prashant Naresh, Dr.Anuradha, Yogesh Kumar Sharma Emerging Technologies and Cyber Security:New Horizons of Cyber Security SolutionsNeha Tyagi, Hoor Fatima, Nitin Rakesh 3D Printing Procedures: Explore the Endless possibilities of 3D Object Design, Modelling and ManufacturingRajesh Pant, Pankaj Negi, Jasmeet Kalra, Sandeep TiwariMultimedia Big Data:The Multimedia Big data impact on Data Storage, Management and Security Strategies for Data Analytics Fatima Ziya, Meenu Shukla, Sharmila, Umang Kant, Jawwad ZaidiVoice Assistants and Chat Bots: Hands on Essentials of UI & Feature Design Development and TestingPavi Saraswat, Bharat Bhardwaj, Prashant Naresh, Alaknanda Ashok, Raja Kumar, Manish KumarFuture Communication Networks: Architecture, Protocols and Mechanisms for the Next generation Internet Dhananjay Kumar, Sangram Ray, Sharmistha AdhikariIndex
"A Chapman & Hall book."
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Computer science -- Technological innovations; COMPUTERS / General; COMPUTERS / Computer Science; COMPUTERS / Computer Engineering